Evolution and standardization progress for NR MIMO enhancement - Nanxi LI; Jianchi ZHU; Jing GUO; Hang YIN; Xiaoming SHE (Dianxin kexue)
As one of the key technologies of 5G , massive multiple-input multiple-output (MIMO) has played an important role in the commercial deployment of 5G networks.Based on the deployment experience of 5G systems, 3GPP Release 17 has done a series of standardization work on MIMO evolution enhancement.Focusing on 3GPP standardization work, the standardization progress of related MIMO enhancement schemes, especially for multi-beam enhancement and multi-TRP enhancement, was introduced and analyzed.In the end, potential future work of 3GPP Release 18 MIMO enhancement was summarized.